Comprehensive Analysis of Motor Deficits after Glioma Surgery having Integrated Exoscopic Neuronavigation, fMRI and DTI at Punjab Institute of Neurosciences, Lahore - Nawaz, Bakht; Shah, Syed Shahzad Hussain; Noman, Hamza; Adeeb Ul Hassan; Khosa, Hassan Ali Khosa; Usman Ahmad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of motor deficits following glioma surgery using integrated exoscopic neuro-navigation, fMRI, and DTI, assessed by the MRC power scale at a tertiary care hospital in Lahore. Study Design: Descriptive longitudinal study. Study place & Duration: Department of Neurosurgery unit 2, Punjab Institute of Neurosciences, Lahore from March 25, 2025 to June 25, 2025. Methodology: A total of 64 patients were enrolled and their demographics were recorded. Following admission, baseline investigations and necessary preoperative workup were conducted. Functional MRI and Diffusion Tensor Imaging were performed. After obtaining anesthesia clearance, patients were scheduled for elective surgery in the neurosurgery operating theater. Surgeries were carried out by the neurosurgical team under neuronavigation guidance, with careful attention to preserving critical tracts and motor eloquent areas. On the first postoperative day, motor power was evaluated using the Medical Research Council (MRC) power scale. Results: The mean age of the patients was 31.20 ± 8.99 years. There were 30 (46.9%) male and 34 (53.1%) female patients. The mean MRC score on the first day was 4.75 ± 0.73, which improved to 4.87 ± 0.57 by the end of the first month. On the 1st month follow-up, motor deficit was observed in 4 (6.25%) patients glioma surgery with integrated exoscopic neuro-navigation, fMRI, and DTI. Conclusion: It was concluded that the chances of motor deficits by using the MRC power scale after glioma surgery.